Implementasi Model Pembelajaran Kooperatif Tipe Team Assisted Individualization untuk Meningkatkan Kemampuan Pemahaman Matematis Siswa - Nunu Nurhayati (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2015)
ABSTRACT  This study aims to determine (1) whether math model of cooperative learning TAI type can improve significantly students' mathematical understanding; (2) how the activities of students and teacher during the learning process; (3) whether the learning model used in improving the ability of mathematical understanding can achieve mastery of student learning; and (4) how the students' response to the application of learning model. This research is a classroom action research (PTK) carried out in three cycles. Research subjects class VIII C SMP Islam Al Azhar 5 Cirebon totaling 25 students. Instruments used in the form of test capabilities instrumental and relational understanding of mathematical student, activity observation sheet of students and teachers, and questionnaires. The results showed, with a model of cooperative learning TAI can improve students' mathematical understanding. This is evidenced by the increase in the results of the pretest to posttest increased understanding of students' mathematical abilities significantly. This is supported by an increase in the average value of students each cycle. Activities of students and teacher during learning quite well and has increased in each cycle. The percentage of students activity increased from the first cycle, second cycle and third cycle in the amount of 57.5 %, 72.5 % and 82.5 %. Activities of students and teacher is getting better at every meeting. Increasing the ability of mathematical understanding can achieve mastery learning students. This is evidenced from the results of the pretest obtained 3 students who completed (12%), the first cycle were 17 students who completed (68%), the second cycle were 19 students (76%) completed, the third cycle as many as 21 students (84%) completed, and postes 22 students (88%) with a value above the KKM. Based on the questionnaire, most students give a good attitude and response to learning with cooperative learning model of TAI as the guidance provided by the teacher individually and the help of friends in the group. TAI model of cooperative learning will be more effective in teaching the material with a deeper level of understanding and ability given to the subject heterogeneous students.  Keywords:      Cooperative Learning Model Team Assisted Individulization, The Ability of Students' Mathematical Understanding.